Socioeconomic Status, Individual Modernity, Economic Literacy, and Consumer Rationality of Millennial Generation - Muhammad Hasan; Nur Arisah; Nurdiana Nurdiana; Tuti Supatminingsih; Sri Indah Nikensari (Jurnal Economia, 2022)
AbstractThis study was designed to reveal the effect of socioeconomic status, individual modernity, and economic literacy on consumer rationality of the millennial generation, either directly or indirectly. It used a quantitative approach, and was designed as an explanatory study. It involved 362 samples using proportional random sampling from 3867 millennial generation students from across 10 faculties, and 149 study programs at Universitas Negeri Makassar. The research data was collected through a questionnaire that had been tested for its validity and reliability. Then, it was analyzed using Structural Equation Modeling analysis. It was found out that (1) socioeconomic status, individual modernity, and economic literacy have a positive and significant effect on consumer rationality; (2) socioeconomic status and individual modernity have a positive and significant effect on economic literacy; and (3) socioeconomic status and individual modernity have a positive and significant effect on consumer rationality through economic literacy of millennial generation.Keywords: Socioeconomic status, individual modernity, economic literacy, consumer rationality, millennial generation.Status Sosial Ekonomi, Modernitas Individu, Literasi Ekonomi, dan Rasionalitas Konsumen Generasi MilenialAbstrakKajian ini didesain untuk mengungkap pengaruh status sosial ekonomi, modernitas individu, dan literasi ekonomi terhadap rasionalitas konsumen generasi milenial, baik secara langsung maupun tidak langsung. Kajian ini menggunakan pendekatan kuantitatif, dan dirancang sebagai kajian eksplanatori. Kajian ini mengambil informasi dari 362 sampel secara proportional random sampling dari 3867 mahasiswa generasi milenial yang tersebar di 10 fakultas, dan 149 prodi dalam lingkup Universitas Negeri Makassar. Data dikumpulkan melalui angket yang telah diuji validitas dan reliabilitasnya, kemudian dianalisis menggunakan analisis Structural Equation Modeling. Hasil kajian ini menunjukkan bahwa (1) status sosial ekonomi, modernitas individu, dan literasi ekonomi berpengaruh positif dan signifikan terhadap rasionalitas konsumen; (2) status sosial ekonomi dan modernitas individu berpengaruh positif dan signifikan terhadap literasi ekonomi; dan (3) status sosial ekonomi dan modernitas individu berpengaruh positif dan signifikan terhadap rasionalitas konsumen melalui literasi ekonomi generasi milenial.Kata kunci:Status sosial ekonomi, modernitas individu, literasi ekonomi, rasionalitas konsumen, generasi milenial.